133k views
4 votes
2(a − 4) = 4a − (2a + 4)

User RonyLoud
by
5.3k points

2 Answers

4 votes

Answer:

No solution

Explanation:

User Yolande
by
5.7k points
2 votes

Answer:

x = no solution

Explanation:

Step 1: Write equation

2(a - 4) = 4a - (2a + 4)

Step 2: Solve for a

Distribute: 2a - 8 = 4a - 2a - 4

Combine like terms: 2a - 8 = 2a - 4

Subtract 2a on both sides: -8 ≠ -4

∴ x = no solution

User Nneko
by
4.7k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.